Racial and Sex Differences in the Response to First-Line Antihypertensive Therapy - Clemmer, John S.; Pruett, W. Andrew; Lirette, Seth T. (Frontiers in Cardiovascular Medicine, 2020)
Objective: As compared to whites, the black population develops hypertension (HTN) at an earlier age, has a greater frequency and severity of HTN, and has poorer control of blood pressure (BP). Traditional practices and treatment efforts have had minor impact on these disparities, with over a 2-fold higher death rate currently for blacks as compared to whites. The University of Mississippi Medical Center (UMC) is located in the southeastern US and the Stroke Belt, which has higher rates of HTN and related diseases as compared to the rest of the country. Methods: We retrospectively analyzed the UMC’s Research Data Warehouse, containing >30 million electronic health records from >900,000 patients to determine the initial BP response following the first prescribed antihypertensive drug. Results: There were 5,973 white (45% overall HTN prevalence) and 10,731 black (57% overall HTN prevalence) patients who met criteria for the study. After controlling for age, BMI, and drug dosage, black males were overall less likely to have controlled BP (defined as <140/90 mmHg) and were associated with smaller falls in BP as compared to whites and black females. Blockers of the renin-angiotensin system (RAS) failed to significantly improve odds of HTN control versus the untreated group in black patients. However, our data suggests that these drugs do provide significant benefit in blacks when combined with THZ, as compared to untreated and as compared to THZ alone. Conclusion: These data support the use of a single-pill formulation with ARB or ACE inhibitor with a thiazide in blacks for initial first-line HTN therapy and suggests that HTN treatment strategies should consider both race and gender. Our study gives a unique insight into initial antihypertensive responses in actual clinical practice and could have an impact in BP control efficiency in a state with prevalent socioeconomic and racial disparities.